2021
DOI: 10.3390/s21227509
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating Heterogeneous Devices and AI Services as Virtual Sensors for Secure Cloud-Based IoT Applications

Abstract: The concept of the cloud-to-thing continuum addresses advancements made possible by the widespread adoption of cloud, edge, and IoT resources. It opens the possibility of combining classical symbolic AI with advanced machine learning approaches in a meaningful way. In this paper, we present a thing registry and an agent-based orchestration framework, which we combine to support semantic orchestration of IoT use cases across several federated cloud environments. We use the concept of virtual sensors based on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, other aspects that, although not unique to IoTSs, are essential in this type of system, such as the incorporation of artificial intelligence (AI) techniques to help the system in decision-making and to be context-aware, i.e., it reacts appropriately according to the context or the existing conditions in the environment [ 39 , 42 ]. Therefore, and if we also consider the heterogeneity of the components and application domains of IoTSs [ 76 , 77 ], it is obvious to conclude that professionals from different areas should be part of their development team in order to carry out the activities included in the different stages of its development, either to act throughout the whole life cycle or to carry out specific tasks [ 78 ].…”
Section: Methodologies Designed For the Development Of Iotssmentioning
confidence: 99%
“…Moreover, other aspects that, although not unique to IoTSs, are essential in this type of system, such as the incorporation of artificial intelligence (AI) techniques to help the system in decision-making and to be context-aware, i.e., it reacts appropriately according to the context or the existing conditions in the environment [ 39 , 42 ]. Therefore, and if we also consider the heterogeneity of the components and application domains of IoTSs [ 76 , 77 ], it is obvious to conclude that professionals from different areas should be part of their development team in order to carry out the activities included in the different stages of its development, either to act throughout the whole life cycle or to carry out specific tasks [ 78 ].…”
Section: Methodologies Designed For the Development Of Iotssmentioning
confidence: 99%
“…Cloud platform (Topic 2) addresses the use of sensors and cloud servers for data collection. In particular, this topic covers sensing technologies necessary for supporting efficient data collection (Kwon and Seo 2022) and frameworks for virtual sensor configurations to collect data via multiple devices (Alberternst et al 2021). Learning technology (Topic 3) addresses the machine learning algorithms can be used in various AI service areas (e.g., smart city service and healthcare service), such as deep learning models for image classification and segmentation (Lee et al 2022b;Tseng et al 2021) and federated learning models for privacy protection of AI services (Rodríguez-Barroso et al 2020).…”
Section: Key Topics (12) In the Ai Service Literaturementioning
confidence: 99%
“…To sum up, the research on Federated Learning mainly focuses on privacy protection [14][15][16][17] and incentive mechanism [18][19][20][21]. At present, the application of Federated Learning in market segments is also gradually developing [22][23][24]. However, there are few examples of literature on the application of Federated Learning to forecasting [25][26][27][28][29]; especially, the application of Federated Learning to the sustainable development research of e-commerce enterprise demand forecasting has not yet been found.…”
Section: Federated Learningmentioning
confidence: 99%